Cyanidin-3-O-glucoside promotes progesterone secretion by improving cells viability and mitochondrial function in cadmium-sulfate-damaged R2C cells. (June 2019) - Li, Xia; Lu, Jun-Li; Sun, Jian-Xia; Jiang, Xin-Wei; Li, Xu-Sheng; Li, Ye; Jiao, Rui; Tian, Ling-Min; Bai, Wei-Bin
Abstract: Cadmium (Cd) is a poisonous metal that is toxic for male reproduction. Cyanidin-3- O -glucoside (C3G) as typical anthocyanin benefits many organs. In this study, we investigated the protective effects and associated underlying mechanisms of C3G against the toxicity of Cd on male reproduction in rat Leydig cell line R2C cells. Cells were pre-protected with C3G (5–160 μmol/L) for 2 h and then treated with cadmium sulfate (CdSO4 ) (10–160 μmol/L) for 24 h. The results showed that cytotoxicity, mitochondrial damage, superoxide dismutase 2 (SOD2), and overproduction of reactive oxygen species (ROS) in CdSO4 -treated R2C cells were significantly reduced with C3G pre-treatment. Moreover, C3G pre-treatment led to upregulated expression of steroidogenic acute regulatory (StAR) protein and progesterone production. Our study suggests that C3G may be a potential therapeutic agent against Cd-induced reproductive toxicity. Highlights: C3G improved cell morphological changes in CdSO4 -treated R2C cells. C3G enhanced progesterone synthesis by modulating MMP and StAR expression. C3G protected against Cd-caused reproductive injury.